2014
DOI: 10.2478/s11772-014-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Wannier-Stark effect and electron-phonon interaction in macroporous silicon structures with SiO2 nanocoatings

Abstract: We investigated the contribution of electron-phonon interaction to the broadening parameter Γ of the Wannier-Stark ladder levels in oxidized macroporous silicon structures with different concentration of Si-O-Si states (TO and LO phonons). The obtained value of the Wannier-Stark ladder parameter Γ is much less than the djacent level energy evaluated from giant oscillations of resonance electron scattering on the surface states. We determined the influence of broadening on the oscillation amplitude in IR absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…4 a and [23]). The obtained values of the broadening parameter  correspond to those for surface phonon polaritons measured in thin films of IIVI semiconductors [16].…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…4 a and [23]). The obtained values of the broadening parameter  correspond to those for surface phonon polaritons measured in thin films of IIVI semiconductors [16].…”
Section: Resultssupporting
confidence: 70%
“…IR absorption for substrates of oxidized macroporous silicon and macroporous silicon with microporous silicon layer (curves 3, 4) is lower and comparable. Thus, nanocoatings of polyethyleneimine with carbon multiwall nanotubes increase surface depletion [27] and IR absorption of macroporous silicon without nanocoatings and decrease surface accumulation [15,16] for SiO 2 coatings and microporous silicon layer. The Raman spectra of macroporous silicon structures with nanocoatings of polyethyleneimine with carbon multiwall nanotubes (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The interband interaction has been studied and demonstrated that it does not break the Wannier-Stark ladder [18]. The electron-phonon interaction was considered in [21]. According to [18], the phonon damping effect leads to an additional shift towards the phase behavior.…”
Section: Discussionmentioning
confidence: 99%